PENGARUH KETERLIBATAN PADA BUSINESS CENTER,PENDIDIKAN KEWIRAUSAHAAN, DAN PRAKTIK KERJA INDUSTRI TERHADAP MINAT BERWIRAUSAHA SISWA SMK - Arifin, Isfirori Nurhamidah (Jurnal Integrasi dan Harmoni Inovatif Ilmu-Ilmu Sosial, 2024)
Abstract: This observe objectives to decide the impact of involvement in a business center, entrepreneurship education, and business work practices on students' hobby in entrepreneurship. The approach on this take a look at is descriptive quantitative with statistics evaluation the use of multiple linear regression evaluation. the whole population on this observe become 104 elegance XII college students of the net business and marketing branch Vocational High School 1 Turen. The pattern on this have a look at amounted to eighty three college students. The sampling approach uses a proportional random sampling technique through taking random samples from all individuals of the populace. contraptions in the form of questionnaires, statement, and documentation. The results of this study prove that partially involvement in the business center has a positive and significant effect on students' interest in entrepreneurship, entrepreneurship education does not have a positive and significant effect on students' interest in entrepreneurship, and industrial work practices have a positive and significant effect on students' interest in entrepreneurship.